2020
DOI: 10.11628/ksppe.2020.23.3.267
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 2010s Research Trends in Research on Agro-Healing in South Korea

Abstract: Background and objective: Agro-healing is crucial with urban farming in the domestic. It is beyond the conventional agriculture. This study was carried out to assess the 2010s researches on domestic agro-healing and predict the future direction of agro-healing development. Methods: Among the articles published from 2010 to 2018, we collected some articles by searching keywords including agro-healing, garden activity, gardening, horticultural activity, horticultural program, horticultural therapy, plant effect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…When examining the above analysis findings, which were grouped based on sub-criteria per main criterion, all three items (community service, which featured the highest complex weight; social rehabilitation, which ranked 2nd; and treatment and rehabilitation, which ranked 3rd) fell within "agro-healing service industry" as the main criterion. Jeong et al (2020) reported that anyone can become a target of agro-healing, even if they do not have specific physical or emotional problems, and that there should be widespread awareness that anyone can experience agro-healing activities. This is in line with the fact that community serv-ice showed the highest complex weight among the 11 sub-criteria.…”
Section: Ahp Analysismentioning
confidence: 99%
“…When examining the above analysis findings, which were grouped based on sub-criteria per main criterion, all three items (community service, which featured the highest complex weight; social rehabilitation, which ranked 2nd; and treatment and rehabilitation, which ranked 3rd) fell within "agro-healing service industry" as the main criterion. Jeong et al (2020) reported that anyone can become a target of agro-healing, even if they do not have specific physical or emotional problems, and that there should be widespread awareness that anyone can experience agro-healing activities. This is in line with the fact that community serv-ice showed the highest complex weight among the 11 sub-criteria.…”
Section: Ahp Analysismentioning
confidence: 99%
“…Agro-healing, which refers to agricultural activities using farm landscapes and resources to improve physical and mental health of people today, is actively studied in terms of application in Korea, led by the Rural Development Administration (Kim, 2019). Jeong et al (2020) examined the different effects of agro-healing and discovered that agro-healing had active therapeutic effects on psychological and emotional variables such as stress, depression, and self-esteem regardless of age. Moreover, doing various five-senses activities in wide and unstandardized spaces such as care farms had better effect on reducing children's daily stress than small and standardized spaces, thereby helping their emotional development (Kim and Koo, 2019).…”
Section: Introductionmentioning
confidence: 99%